RUSSIAN PRACTICE OF USE OF INTERNATIONAL FACTORING TRANSACTIONS - Ilya E. Pokamestov (Статистика и экономика)
The article focuses on some aspects of use of international factoring transactions and its use in the Russian practice. The main indicators of international factoring industry among developed countries are reviewed. The main reasons of the small spread of the international factoring in Russia are identified.